Coordination of translational control and protein homeostasis during severe heat stress - Khaimov, Valeria; Hofmann, Sarah Ulrike; Druffel-Augustin, Silke; Mogk, Axel; Tyedmers, Jens; Stoecklin, Georg; Bukau, Bernd (Current biology, 2013)
Background - Exposure of cells to severe heat stress causes not only misfolding and aggregation of proteins but also inhibition of translation and storage of mRNA in cytosolic heat stress granules (heat-SGs), limiting newly synthesized protein influx into overloaded proteome repair systems. How these two heat stress responses connect is unclear. - Results - Here, we show that both S. cerevisiae and D. melanogaster heat-SGs contain mRNA, translation machinery components (excluding ribosomes), and molecular chaperones and that heat-SGs coassemble with aggregates of misfolded, heat-labile proteins. Components in these mixed assemblies exhibit distinct molecular motilities reflecting differential trapping. We demonstrate that heat-SG disassembly and restoration of translation activity during heat stress recovery is intimately linked to disaggregation of damaged proteins present in the mixed assemblies and requires Hsp104 and Hsp70 activity. - Conclusions - Chaperone-driven protein disaggregation directly coordinates timing of translation reinitiation with protein folding capacity during cellular protein quality surveillance, enabling efficient protein homeostasis.